PKM Pelatihan dan Pengembangan Media Pembelajaran Biologi Berbasis Flipbook pada Pokok Bahasan Sistem Koordinasi - Marisha Ayuardini; Yulistiana Yulistiana; Endah Diah Parwati; Rahmat Johansyah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Along with the development of the use of technology in every line of human life, it also requires Biology learning media that can help students understand the subject matter. At present, a technological innovation has developed that can be utilized as one of the biology learning media, namely Flipbook. Biology learning media using Flipbook is considered to be able to improve the ability to understand concepts to students. Based on the advantages of various features in Flipbook and reviewed from the learning needs required by students at SMA Jagakarsa, the use of Flipbook media can be considered appropriate for use; both for students and teachers, because it can objectify learning materials that comprehensive but easy to understand.